The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1982-0224-20180022
|View full text |Cite
|
Sign up to set email alerts
|

Fish beta diversity responses to environmental heterogeneity and flood pulses are different according to reproductive guild

Abstract: In floodplain communities, beta diversity is influenced by different factors; however, environmental heterogeneity and floods are believed to be particularly influential. The influence of environmental heterogeneity and floods on beta diversity may vary among guilds that present different ecological traits. This study evaluated the correlation between the environmental heterogeneity and flood periods and the beta diversity of trophic and reproductive guilds of fish assemblages. Sampling was conducted quarterly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…The annual flood pulse promotes fish dispersal, frequent restructuring of fish assemblages over variable spatial scales, homogenization of assemblage composition, and a decline in β diversity. Gutiérrez et al () evaluated the effects of environmental heterogeneity and floods on fish β diversity in a floodplain reach of the Upper Paraná River and found that for species with high dispersal capabilities, there was no clear relation between the flood pulse, environmental heterogeneity, and β diversity. Only those fishes with limited dispersal rates, especially substrate‐nesting species with brood care, revealed patterns associated with hydrological and environmental variation.…”
Section: Discussionmentioning
confidence: 99%
“…The annual flood pulse promotes fish dispersal, frequent restructuring of fish assemblages over variable spatial scales, homogenization of assemblage composition, and a decline in β diversity. Gutiérrez et al () evaluated the effects of environmental heterogeneity and floods on fish β diversity in a floodplain reach of the Upper Paraná River and found that for species with high dispersal capabilities, there was no clear relation between the flood pulse, environmental heterogeneity, and β diversity. Only those fishes with limited dispersal rates, especially substrate‐nesting species with brood care, revealed patterns associated with hydrological and environmental variation.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of forest to pasture is also expected to have a negative impact on species with specific functional traits, such as parental care, benthic habits, and invertivorous or piscivorous diets (Casatti et al., 2012). Parental care, for example, may depend on the availability of allochthonous debris to provide shelter and is typical of species with a reduced dispersal capacity (Gutiérrez et al., 2018). The reduced heterogeneity in the substrate of the streambed may also be unfavourable to benthic species (Teresa et al., 2015), while many insect and fish prey may disappear due to the absence of riparian vegetation (Woodward & Hildrew, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, la secuencia hidrológica producto de los pulsos de inundación (Junk, et al, 1989) somete a las comunidades ícticas a sucesiones ecológicas regulares y repetidas y establece relaciones recíprocas entre las corrientes de agua y los cuerpos lénticos (Lewis, et al, 2000;Bozelli, et al, 2015). En consecuencia, estas comunidades logran dispersarse en todos los ambientes acuáticos disponibles a medida que los ecosistemas fluctúan (Lacambra & Pinilla, 2004;Gutiérrez, et al, 2018).…”
Section: Introductionunclassified